Barro que conta histórias e histórias contidas no barro: estudo das cerâmicas etnográficas Kariri-Xokó e Pankararu - Silva, Amanda Barreto da (2022)
Contribute with the indigenous history from the Brazilian northeast, to those associated with the Macro-Jê languages, it is the main point of this study. Through the Ethnographic Collection Carlos Estevão de Oliveira, situated in the Pernambuco State Museum, potteries examined were produced in the begging of 20th century by the indigenous people Kariri-Xokó and Pankararu. The analysis of the technical style from the potteries set enabled notice them as a expression of identities, memories, and histories. The potteries enabled discussions about the contexts of their productions and use, this opened space to reflections over indigenous communities of practices and cosmologies. Besides that, here inserts to the discussion with the relation of these with the editor of the ethnographic collection, Carlos Estevão de Oliveira, as well as the changes imposed by the museum setting because of the transformation of the pottery in a documentobject.